Assessment of levels of awareness towards blood donation in Saudi Arabia - Alharbi, Saleh Hadi (AIMS Public Health, 2018)
BACKGROUND: blood products is an interesting term as all blood and blood transfusion procedures carry risk even with advance screening of donors and donated blood. In Saudi Arabia voluntary donors are either the only source or not, the other source is paid donors and the lack of volunteers represents a major challenge. This is usually attributed to low community awareness regarding voluntary blood donation. Therefore, the objective of this study was to assess the levels of awareness towards blood donation in northern Saudi Arabia. METHODOLOGY: in this descriptive cross sectional survey, data about blood donation were obtained from 717 Saudi volunteers living in the city of Hail, Saudi Arabia. A Purposeful questionnaire was designed and used for obtaining of the necessary data. RESULTS: When asking the participants to rate the level of awareness about blood donation in Saudi Society, the majority of participants categorized the levels as good followed by very good and poor, representing 48.8%, 29.3%, and 22% participants, respectively. CONCLUSION: the broad concept of blood donation is still poor in Saudi Arabia. Further educational plans are needed to raise the level of awareness and increase the perception of blood donation among Saudi population. Efforts should be made to involve females in blood donation duties.